Failure of two consecutive annual treatments with ivermectin to eradicate the reindeer parasites (Hypoderma tarandi, Cephenemyia trompe and Linguatula arctica) from an island in northern Norway. - Nilssen, Arne C.; Hemmingsen, Willy; Haugerud, Rolf E. (Nordisk organ for reinforskning, 2002)
The highly efficient endectocide ivermectin is used to reduce the burden of parasites in many semidomestic reindeer herds in northern Fennoscandia. In the autumn of 1995 and 1996 all reindeer on the island of Silda (42 km2) were treated with ivermectin in an attempt to eradicate the warble fly (Hypoderma (=Oedemagena) tarandi (L.)), the nose bot fly (Cephenemyia trompe (Modeer)) (Diptera: Oestridae) and the sinus worm (Linguatula arctica Riley, Haugerud and Nilssen) (Pentastomida: Linguatulidae). Silda is situated 2-3 km off the mainland of Finnmark, northern Norway, and supports about 475 reindeer in summer. A year after the first treatment, the mean abundance of H. tarandi was reduced from 3.5 to 0.6, but a year after the second treatment the mean abundance unexpectedly had increased to 4.5. After one year without treatment, the mean abundance and prevalence of the three target parasites were at the same level, or higher, than pre-treatment levels. The main hypothesis for the failure to eliminate the parasites is that gravid H. tarandi and C. trompe females originating from untreated reindeer in adjacent mainland areas dispersed to the island during the warm summer of 1997 (possibly also in 1998). As these oestrids are strong flyers, it may not be too difficult for them to cross >2-3 km of oceanic waters. There are no good explanations for the failure to eradicate L. arctica, but the results indicate that there may be elements in its life cycle that are unknown. The conclusion of the study is that it may be difficult or impossible to eradicate these parasites permanently, even locally such as on islands unless adjacent areas on the mainland are also cleared.